FORMULASI TABLET EFFERVESCENT EKSTRAK RIMPANG JAHE EMPRIT (Zingiber officinale Rosc.) DENGAN VARIASI KADAR ASAM SITRAT DAN ASAM TARTRAT - Mufrod Mufrod; Sekararum Diah Kartikasari; Yosi Bayu Murti (Faculty of Pharmacy, Universitas Gadjah Mada, 2015)
Ginger (Zingiber officinale Rosc.) has efficacy as an anti-emetic. Ginger rhizome is usually consumed as instant beverages, so that need to be made into a dosage form that more effective, efficient and attractive. This research aims to formulate ginger into effervescent tablets by using variation of the levels of citric acid and tartaric acid. Dried extract of ginger was made with percolation method using ethanol 70% and evaporated using spray dryer. Extract was made for 5 formulas with variation of acid source using smelting method. Granules were tested its physical properties include flow time, tap index, angle of repose, water absorption, compactibility, mass density, water content, and total phenolic level. Granules were compressed become tablets and tested for physical properties include weight uniformity, friability, hardness, dissolve time, flavor response test and total phenolic level. Data were analyzed with Anova One Way using 95% confidence level. The result shown that formula III was the best formula because it meets the physical requirements of granules and tablets. While the formula V (100% tartaric acid) was a formula that provides the greatest stability phenolic levels.